Cuidado na perspectiva de homens: um olhar da enfermagem - Silva, Silvana de Oliveira (2010)
In the last decades the men was studyng target in different knowledge áreas by virtue of the morbimortality increasing and the apparent reluctance of the man about bewaring thenselves and incipient worry with health. In this perspective the present study had as objective to figure out the knowledges and the caution practices developed by men age 20 and 30 years old, residents in the coverence área of the family s stractegic health Monsenhor Assis in municipal district of Santiago-Rs. The proposal justified itself by perceive, on assistance quotidian and of teaching learning, emphasis to experiences relationed to women s health and of caring thenselves or the other. However to anchieve the proposal objective took effect a descritive exploratory qualitative research. The data collection was realized by means of narrative interview and observation. In this research participated, thirteen men among 20 and 30 years old residents in the coverence área of ESF Monsenhor Assis whon haven t refered morbity and accepted to participate of the research. The local of the data collection by solicitation of the subjects was basicaly at their domiciles, searching of to reach the manifested meanings and latents of the datas, to resulted a content analisis of type tematic proposal by Minayo (2008) from wich emerged Five analitical categories. The results of this study demonstrate that the man conceive caring of coverent and singular form, which constitute thenselves creatures caring as thenselves as the other and wich practice it by mean of diversified actions and attitude. Even point to the fragilities existents on health services that difficult the Access of those subjects on the Health Sisten s Net. To make respect that this research hás a big prominence not even for the nursing, but for all society at all, since that gave visibility to those subjects which culturaly and socialy till then are conceived from a unique model of masculinity. However, make suggested for the nurses that in their assistential and managemential actions be sensitive to the perspective of the man with regard to the care of these actions be suitable with the needs of the subjects. Therefore, to become indispensable to promote spaces of reflection as in the formation of health professionals as in the municipal districts wich hás the pretension to stablish the National Politic of Integral Attention to Men s Health.